Hypoperfusion intensity ratio correlates with angiographic collaterals in acute ischaemic stroke with M1 occlusion. (13th March 2020) - Guenego, A.; Fahed, R.; Albers, G. W.; Kuraitis, G.; Sussman, E. S.; Martin, B. W.; Marcellus, D. G.; Olivot, J.‐M.; Marks, M. P.; Lansberg, M. G.; Wintermark, M.; Heit, J. J.
Abstract : Background and purpose: Among patients with an acute ischaemic stroke secondary to large‐vessel occlusion, the hypoperfusion intensity ratio (HIR) [time to maximum (TMax) > 10 volume/TMax > 6 volume] is a strong predictor of infarct growth. We studied the correlation between HIR and collaterals assessed with digital subtraction angiography (DSA) before thrombectomy. Methods: Between January 2014 and March 2018, consecutive patients with an acute ischaemic stroke and an M1 middle cerebral artery (MCA) occlusion who underwent perfusion imaging and endovascular treatment at our center were screened. Ischaemic core (mL), HIR and perfusion mismatch (TMax > 6 s minus core volume) were assessed through magnetic resonance imaging or computed tomography perfusion. Collaterals were assessed on pre‐intervention DSA using the American Society of Interventional and Therapeutic Neuroradiology/Society of Interventional Radiology (ASITN/SIR) scale. Baseline clinical and perfusion characteristics were compared between patients with good (ASITN/SIR score 3–4) and those with poor (ASITN/SIR score 0–2) DSA collaterals. Correlation between HIR and ASITN/SIR scores was evaluated using Pearson's correlation. Receiver operating characteristic analysis was performed to determine the optimal HIR threshold for the prediction of good DSA collaterals. Results: A total of 98 patients were included; 49% (48/98) had good DSA collaterals and these patients had significantly smaller hypoperfusion volumes (TMax > 6 s, 89 vs. 125 mL; P  = 0.007) and perfusion mismatch volumes (72 vs. 89 mL; P  = 0.016). HIR was significantly correlated with DSA collaterals (−0.327; 95% confidence interval, −0.494 to −0.138; P  = 0.01). An HIR cut‐off of <0.4 best predicted good DSA collaterals with an odds ratio of 4.3 (95% confidence interval, 1.8–10.1) (sensitivity, 0.792; specificity, 0.560; area under curve, 0.708). Conclusion: The HIR is a robust indicator of angiographic collaterals and might be used as a surrogate of collateral assessment in patients undergoing magnetic resonance imaging. HIR <0.4 best predicted good DSA collaterals.